PEMANFAATAN FAST TRACK LEGISLATION SEBAGAI MODEL PENDEKATAN PENEGAKAN HUKUM DALAM TINDAK PIDANA KORUPSI - Wiwik, Mariani (Gapenas Publisher, 2024)
Law enforcement in Indonesia is increasingly complex with the increase in cases of extraordinary crime (EOC). Therefore, innovation in criminal law is needed that remains in line with other regulations. Several countries such as the United Kingdom, the United States, New Zealand, and Ecuador have implemented the Fast Track Legislation mechanism to fill the legal gap. Indonesia itself does not have this mechanism formally, although in practice there are indications of its implementation, which can give rise to the presumption of the tyranny of legislation in the formation of laws. The research method used is philosophical juridical with a descriptive fanatical approach, relying on primary and secondary data obtained through literature studies. Fast Track Legislation can be an alternative to the Perppu while still ensuring public supervision in its formation. Various methods of Fast Track Legislation are applied in the world based on regulations, legal subjects, and supervisory mechanisms. Unfortunately, this idea cannot be implemented immediately in Indonesia without an in-depth study of the reform of the legal system, institutions, and its supporting devices